Spatial distribution of the ingredients of desert tourism in the western plateau region of Iraq: (Presentation of Arab experiences in the field of desert tourism) - Adnan Hasson, Luay (Al-Adab Journal, 2020)
The research aimed to detection the elements of tourism attraction in the western plateau desert plateau that Located the western and southwestern sections of Iraq, and the research has shown that the region possesses almost integral components for the tourism offer, as it witnessed a diversity in natural ingredients that were represented by the unique geographical location and diversity in geomorphological and biological diversity as well as The availability of human resources, which were represented by historical, heritage and religious sites, hospitality and complementary auxiliary services. The research also demonstrated the possibility of establishing many forms of tourism in the study area, such as desert, environmental and adventure tourism. Conferences, scientific, religious, cultural and other forms of tourism. The research also touched on a number of countries ’experiences in this field in order to benefit from them in the process of tourism investment in the future. By investing these ingredients and supporting the process of tourism development